The Changing Rakhain Community of Bangladesh: A Perspective of Balancing Traditions and Technologies in Safeguarding Weaving Industry (Social Science Review, 2026)
The indigenous Rakhain community living in Bangladesh is renowned for their outstanding skills in manufacturing high-quality textiles. This community, who crossed the turbulent Bay of Bengal several hundred years ago to save their lives from a tyrant dynast, had a long tradition of textiles craftsmanship in their ancestral homeland. Rakhain artisans initiated textile production in Bangladesh to cater to the demand within the community, and as time went on, many Bengalis grew interested in their phenomenal handwoven items. This study delves into the underlying causes of the deteriorating state of handloom artisanship in Rakhain enclaves and how handwoven fabrics continue to be appealing in contrast to modern fabrics. Using purposive sampling and a semi-structured approach, this study has taken face-to-face interviews for data collection. The findings of this research show a lack of standardization and collaboration with times and markets, as well as changing technologies and diversification of needs, are responsible for this distressing situation. This research unveils several actionable insights for community leaders, NGOs, and government to revitalize this century-old tradition.Social Science Review [The Dhaka University Studies, Part-D], Vol. 42, No.2, December 2025, pp. 187-210